Praperadilan sebagai Upaya Perlindungan Hak Konstitusional Tersangka terhadap Penetapan Tersangka - Roosdiana Marthina Leode; Marten Bunga; Yusrianto Kadir (International Forum of Researchers and Lecturers, 2026)
Premature designation of a suspect in the criminal justice process may cause significant legal, social, and reputational harm because such status can result in restrictions on individual rights and public stigma. This study examines the role of pretrial proceedings in protecting the constitutional rights of suspects and formulates the juridical parameters for determining when a suspect designation can be considered premature. The research employs a normative legal method using statutory, conceptual, and case approaches through library research of legislation, court decisions, and legal doctrines. The findings indicate that pretrial proceedings serve as a judicial control mechanism over investigative actions, particularly following the expansion of pretrial jurisdiction that enables courts to assess the legality of suspect designation. A designation may be deemed premature if it lacks at least two valid pieces of evidence, is not preceded by lawful investigative procedures, or violates the principle of due process of law. However, the effectiveness of pretrial proceedings remains limited because judicial review is largely formal, conducted within a short time frame, and unable to fully restore the suspect’s reputation. Therefore, clearer procedural guidelines, enhanced legal capacity of judges and investigators, and reforms to criminal procedural law are necessary to strengthen constitutional rights protection.